Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content: 1. Molecular Weight Determination of L-asparaginase from Bacillus licheniformis Dr. Vivian Ramzi Daifallah, Dr. Sabah Nassib Yazji, Dr. Lina Abdulkarim Al-Amir 2. Environmental Toxins and Their Organ-Specific Effects: A Comprehensive Review of Human Exposure and Accumulation Dr. Emam Atiyah Ibadi, Mr. Hussein Kamil Awad, Ms. Lujain Ibrahim Hussain